Can the Non-native Salt Marsh Halophyte Spartina alterniflora Threaten Native Seagrass (Zostera japonica) Habitats? A Case Study in the Yellow River Delta, China - Yue, Shidong; Zhou, Yi; Xu, Shaochun; Zhang, Xiaomei; Liu, Mingjie; Qiao, Yongliang; Gu, Ruiting; Xu, Shuai; Zhang, Yu (Frontiers in Plant Science, 2021)
Seagrass meadows are critical ecosystems, and they are among the most threatened habitats on the planet. As an anthropogenic biotic invader, Spartina alterniflora Loisel. competes with native plants, threatens native ecosystems and coastal aquaculture, and may cause local biodiversity to decline. The distribution area of the exotic species S. alterniflora in the Yellow River Delta had been expanding to ca.4,000 ha from 1990 to 2018. In this study, we reported, for the first time, the competitive effects of the exotic plant (S. alterniflora) on seagrass (Zostera japonica Asch. & Graebn.) by field investigation and a transplant experiment in the Yellow River Delta. Within the first 3 months of the field experiment, S. alterniflora had pushed forward 14 m into the Z. japonica distribution region. In the study region, the area of S. alterniflora in 2019 increased by 516 times compared with its initial area in 2015. Inhibition of Z. japonica growth increased with the invasion of S. alterniflora. Z. japonica had been degrading significantly under the pressure of S. alterniflora invasion. S. alterniflora propagates sexually via seeds for long distance invasion and asexually by tillers and rhizomes for short distance invasion. Our results describe the invasion pattern of S. alterniflora and can be used to develop strategies for prevention and control of S. alterniflora invasion.